Assessing the viability of heart rate variability as an objective and comprehensive indicator of chronic non-specific neck pain. - Chao Zhang; Hai-Peng Xu; Hui-Fang Zheng; Xiao-Lian Wu; Hong-Gen Du; Xin Jin (PLoS ONE)
Background This study investigates heart rate variability (HRV) in chronic nonspecific neck pain (CNNP) patients, revealing reduced HRV linked to pain intensity, anxiety, and cervical instability, and proposes HRV as an objective biomarker for comprehensive CNNP assessment. Method According to the inclusion and exclusion criteria, 80 patients were included in the experimental group. In addition, 80 healthy individuals matched for age, sex, and other basic information were selected as the control group. The clinical outcome of patients was assessed using the visual analog scale and the self-rating anxiety scale. Subsequently, imaging studies were performed to assess cervical stability (atlantoaxial deviation, axis rotation), osteophytes, physiologic curvature, and disc herniation in patients. The frequency domain (low frequency, high frequency, and their ratio) and time domain (standard deviation of all normal-to-normal QRS intervals) HRV indexes were obtained from all subjects using the heart rate meters. Results All HRV indexes were significantly lower in patients compared to controls, and pain and anxiety further reduced HRV indexes in patients. Pain intensity, anxiety, and disc herniation were significantly correlated with all the HRV indexes. Mild instability was not correlated with the HRV, but instability reaching a certain level (atlantoaxial deviation >0.1 mm or rotation of the axis >2 mm) was significantly correlated with the HRV indexes. Discussion Chronic nonspecific neck pain associated with autonomic nervous system dysfunction, and heart rate variability provides an objective and comprehensive assessment of chronic nonspecific neck pain.